Infants’ Learning of Rule-Based Visual Sequences Predicts Language Outcome at 2 Years - Bettoni, Roberta; Riva, Valentina; Cantiani, Chiara; Molteni, Massimo; Macchi Cassia, Viola; Bulf, Hermann (Frontiers in Psychology, 2020)
The ability to learn and generalize abstract rules from sensory input –i.e., Rule Learning (RL)– is seen as pivotal to language development, and specifically to the acquisition of the grammatical structure of language. Although many studies have shown that RL in infancy is operating across different perceptual domains, including vision, no studies have directly investigated the link between infants’ visual RL and later language acquisition. Here, we conducted a longitudinal study to investigate whether 7-month-olds’ ability to detect visual structural regularities predicts linguistic outcome at 2 years of age. At 7 months, infants were tested for their ability to extract and generalize ABB and ABA structures from sequences of visual shapes, and at 24 months their lexical and grammatical skills were assessed using the MacArthur-Bates CDI. Regression analyses showed that infants’ visual RL abilities selectively predicted early grammatical abilities, but not lexical abilities. These results may provide the first evidence that RL mechanisms are involved in language acquisition, and suggest that RL abilities may act as an early neurocognitive marker for language impairments.